Parkinson disease phenotype in Ashkenazi jews with and without LRRK2 G2019S mutations. Issue 14 (15th October 2013) - Alcalay, Roy N.; Mirelman, Anat; Saunders‐Pullman, Rachel; Tang, Ming‐X; Mejia Santana, Helen; Raymond, Deborah; Roos, Ernest; Orbe‐Reilly, Martha; Gurevich, Tanya; Bar Shira, Anat; Gana Weisz, Mali; Yasinovsky, Kira; et al.
ABSTRACT The phenotype of Parkinson's disease (PD) in patients with and without leucine‐rich repeat kinase 2 (LRRK2) G2019S mutations reportedly is similar; however, large, uniformly evaluated series are lacking. The objective of this study was to characterize the clinical phenotype of Ashkenazi Jewish (AJ) PD carriers of the LRRK2 G2019S mutation. We studied 553 AJ PD patients, including 65 patients who were previously reported, from three sites (two in New York and one in Tel‐Aviv). Glucocerebrosidase (GBA) mutation carriers were excluded. Evaluations included the Montreal Cognitive Assessment (MoCA), the Unified Parkinson's Disease Rating Scale (UPDRS), the Geriatric Depression Scale (GDS) and the Non‐Motor Symptoms (NMS) questionnaire. Regression models were constructed to test the association between clinical and demographic features and LRRK2 status (outcome) in 488 newly recruited participants. LRRK2 G2019S carriers (n = 97) and non‐carriers (n = 391) were similar in age and age at onset of PD. Carriers had longer disease duration (8.6 years vs. 6.1 years; P < 0.001), were more likely to be women (51.5% vs. 37.9%; P = 0.015), and more often reported first symptoms in the lower extremities (40.0% vs. 19.2%; P < 0.001). In logistic models that were adjusted for age, disease duration, sex, education, and site, carriers were more likely to have lower extremity onset (P < 0.001), postural instability and gait difficulty (PIGD) (P = 0.043), and a persistent levodopa response for >5 years (P = 0.042). Performance on the UPDRS, MoCA, GDS, and NMS did not differ by mutation status. PD in AJ LRRK2 G2019S mutation carriers is similar to idiopathic PD but is characterized by more frequent lower extremity involvement at onset and PIGD without the associated cognitive impairment. © 2013 International Parkinson and Movement Disorder Society